Representaciones sociales frente al autocuidado en la prevención del cáncer de mama (2009)
ABSTRACT: to understand the social representations of breast cancer in a group of women of Medellin, Colombia, 2007 -2008, and their influence in prevention and self-care practices. Methodology: qualitative study carried out with 19 semi-structured interviews to adult women who have not had breast cancer using the sampling criterion of maximum variation. The analysis is based on grounded theory. Results and discussion: the representations are predominantly aesthetic. The knowledge about self-care practices is vague; scarce information and education are perceived on those issues. Self-examination, mammography and clinical examination are not done, or are done without due frequency. This coincides with other studies. In relation to the possibility of suffering breast cancer, some of them consider their confusion and scarce preparation to deal with it. Women need higher autonomy for self-care and the right to define their health and to impose limits on it. People are responsible for their life styles, regardless non controllable factors. The self-care allows that life goes on and is our contribution to our own existence. Conclusions: in addition to the social representation of breasts as object of attraction, the interviewees have a negative representation of breast cancer. These representations neither foster breast cancer prevention nor contribute to self-care practices. We are puzzled by the fact that had never suffered cancer would describe vividly their concerns about its effects. We think that this is related to a construction of femininity that deserves to be revised.